Гарантії конституційних прав і свобод людини в Україні: шляхи удосконалення - Полянський, Юрій Євгенійович; Полянский, Юрий Евгеньевич; Poljanskij, Jurij (My University, 2009)
In the article the issues of the day of g u a r a n t e e i n g of h u m a n rights and freedoms are considered in sovereign Ukraine. It is s u g g e s t e d to select four levels of g u a r a n t e e i n g on each of which general legal principles are realized. The role of c o u r t s is considered in providing of g u a r a n t e e s of h u m a n r i g h t s and freedoms, t h e w a y s of reformation and perfection of the judicial s y s t e m and public prosecution are offered in Ukraine.
Полянський Ю. Є. Гарантії конституційних прав і свобод людини в Україні: шляхи удосконалення / Ю. Є. Полянський // Наукові праці Одеської національної юридичної академії / голов. ред. С. В. Ківалов ; МОН України, ОНЮА. - Одеса : Юрид. л-ра, 2009. - Т. 8. - С. 178-191.
Keywords: права і свободи людини; гарантії прав і свобод людини; судова система України; прокуратура України; правоохоронна діяльність; права и свободы человека; гарантии прав и свобод человека; судебная система Украины; прокуратура Украины; правоохранительная деятельность; human rights and freedoms; guarantees of human rights and freedoms; judicial system of Ukraine; public prosecution of Ukraine; law-enforcement activity